2021
DOI: 10.1371/journal.pone.0247407
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the farmers’ pro-environmental behavior intention and their rural tourism livelihood in tourist village where its ecological environment is polluted

Abstract: This study examines farmers’ intentions towards pro-environmental behavior in a famous tourist village in China called Guanshan, whose ecological environment is polluted. By adopting the empirically validated norm activation model (NAM) of Schwartz and merging it with Vroom’s expectancy theory, the current research aims to develop a refined framework for understanding the formation of and predicting changes in pro-environmental intention. Field surveys were conducted in Guanshan, which resulted in sample data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…The relationship between Expectancy and Behavioural Intention is found to be positively related ( β = + 0.266). Hence, H4 was accepted and this conforms to earlier works (Tang et al , 2021; Wang et al , 2021). This observation could result from the fact that urban tourists are positively motivated to put enough effort into visiting the national parks, which will give them a palpable sense of accomplishment and remarkably improve their image as practical tourists.…”
Section: Discussionsupporting
confidence: 88%
“…The relationship between Expectancy and Behavioural Intention is found to be positively related ( β = + 0.266). Hence, H4 was accepted and this conforms to earlier works (Tang et al , 2021; Wang et al , 2021). This observation could result from the fact that urban tourists are positively motivated to put enough effort into visiting the national parks, which will give them a palpable sense of accomplishment and remarkably improve their image as practical tourists.…”
Section: Discussionsupporting
confidence: 88%
“…Second, concerning the impact of psychological factors on pro-environmental behaviors, studies found that attitude, place attachment, subjective norms, moral norms, etc., had different degrees of impact on pro-environmental behavior. Related studies were mainly based on the Theory of Planned Behavior (TPB) [ 1 ], the Norm Activation Model (NAM) [ 30 ], and the Value–Belief–norm Theory (VBN) [ 1 ]. Psychological factors were proven to have an excellent explanatory ability in pro-environmental behavior analysis, of which environmental attitude was always defined as a key factor in addressing the complex internal process and psychological mechanisms in farmers’ pro-environmental behavior [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The normative activation model (NAM) was proposed by Schwartz (1981) as a classical model to explain pro-environmental behavior, with more emphasis on the importance of morality (Onwezen and Antonides et al 2013;Kim and Seock 2019;Nordfjaern and Rundmo 2019). The practice of eco-breeding by farmers is a pro-environmental behavior that can be seen as a mixture of self-interest and altruism (Price and Leviston 2014;Liu and Sheng et al 2017;Tang and Liu et al 2021). This study integrates the structure of TPB and NAM and adds interrelationships between past habits and intentions to enhance the predictive power of the proposed framework for explaining In this study, we investigated farmers' intentions to adopt waterfowl eco-breeding practices by using the TPB-NAM integrated model in both the economic and social value dimensions.…”
Section: Introductionmentioning
confidence: 99%